Communicating food policy research: A guidebook - von Grebmer, Klaus; Babu, Suresh Chandra; Rhoe, Valerie; Rubinstein, Michael (International Food Policy Research Institute, 2002)
This manual aims to help researchers enhance their communication skills and encourages them to think about the potential audiences for and beneficiaries of their research at the inception of every project. The manual highlights principles and procedures that have proven successful in presenting research results to peers, colleagues, the media, policymakers, and interest groups. It includes guidelines for targeting and reaching selected audiences as well as exercises for applying those guidelines. It invites researchers, workshop participants, and other readers to use their own recent work to develop immediately useful, usable communication strategies and documents.